N-Glucosylated Compounds: Synthesis of New 1-Tetra-O-acetyl-β-D-glucopyranosyl-3-aryl Thiocarbamides - Korpe, G.V.; Deshmukh, S.P. (Asian Journal of Chemistry, 2010)
Four new 1-tetra-O-acetyl-β-D-glucopyranosyl-3-aryl thiocarbamides have been prepared by interaction of tetra-O-acetyl-β-Dglucopyranosyl isothiocyanate and aryl amines. The identities of these compounds have been established on the basis of IR and NMR spectral analysis and usual chemical transformations. In view of our interest in carbohydrate chemistry we now report the synthesis of some new 1-tetra-O-acetyl-β-D-glucopyranosyl-3-aryl thiocarbamides.